THE ROLE OF LEARNING MOTIVATION AND PARENTAL SUPPORT IN DEVELOPING STUDENT CREATIVITY IN THE INDUSTRIAL REVOLUTION ERA 4.0 - Lely Agustini Nasution; Daharnis; Dina Sukma; Zadrian Ardi (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
In the era of the industrial revolution 4.0 which was marked by technological changes and demands for rapid change, education faced major challenges in developing student creativity. Learning motivation and parental support play a very important role in stimulating students' creativity in this era. This study aims to describe learning motivation and parental support with student creativity in the era of the industrial revolution 4.0. This study uses a quantitative method with descriptive correlation. The population of this study was 479 students of class XI and XII at SMKN 3 Padang, and the sample was 218 students who were selected using a proportional stratified random sampling technique. The research instrument is a Likert scale. The results of the validity test of the learning motivation instrument were 0.441, parental support was 0.442, and student creativity is 0.672. The results of the reliability test of the learning motivation instrument were o.886, parental support was 0.801, and student creativity was 0.846. Data were analyzed using descriptive statistics, simple and multiple regression. The results showed that: (1) on average the description of learning motivation was at a high level, (2) the description of parental support was at a high level, (3) and the description of student creativity in the era of the industrial revolution 4.0 was in the high category, (4) ) there is 7.5% (R=0.275, at significance 0.000) in the relationship between learning motivation and student creativity, (5) there is 7.2% (R=0.268, significance 0.000) in the relationship between parental support and student creativity, (6) there was 11% (R=0.332, at a significance of 0, 000) in the relationship between learning motivation and parental support with student creativity in the era of the industrial revolution 4.0. The implications of this research can be used as a need assessment to create a guidance and counseling service program at SMKN 3 Padang.